Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1149/2.0141610jss
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Extremely Low-k Film Integration Technology with Metal Hard Mask Process for Cu Interconnects

Abstract: High performance copper interconnects using extremely low-k film for the interlayer dielectric with the metal hard mask process and the interfacial surface oxygen treatment between extremely low-k film and liner layer was demonstrated. To suppress the process damage of interlayer dielectric and enlarge the space between vias and lines with a wide margin of lithography process, the robust extremely low-k film with the metal hard mask self-aligned via process was developed. The ultimate low capacitance wiring wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…1. However, the near continuous implementation of new lowk dielectrics with each new technology was not without significant and well documented challenges [107][108][109][110][111] that severely impacted the development of the associated metallization, [112][113][114] patterning, [115][116][117][118][119] and packaging [120][121][122][123] processes needed to fabricate a high yielding metal interconnect. By the mid 2010's, the challenges of implementing new low-k SiOCH ILDs with k ≤ 2.3 had reached a breaking point relative to overall technology development goals for numerous reasons.…”
Section: The End Of Permittivity Scaling?mentioning
confidence: 99%
“…1. However, the near continuous implementation of new lowk dielectrics with each new technology was not without significant and well documented challenges [107][108][109][110][111] that severely impacted the development of the associated metallization, [112][113][114] patterning, [115][116][117][118][119] and packaging [120][121][122][123] processes needed to fabricate a high yielding metal interconnect. By the mid 2010's, the challenges of implementing new low-k SiOCH ILDs with k ≤ 2.3 had reached a breaking point relative to overall technology development goals for numerous reasons.…”
Section: The End Of Permittivity Scaling?mentioning
confidence: 99%
“…Torazawa et al integrated extremely low-k dielectric films and used a hard metal masking process to form copper interconnects. The SiOC(H) films were deposited via PECVD, then irradiated under UV light to remove the porogens [ 8 ]. Lai et al used amorphous carbon ( a -C) to enhance hard masking and lithography capability, and they found that C 2 H 2 -based a -C provided better sidewall step coverage than conventional C 3 H 3 -based a -C [ 9 ].…”
Section: Introductionmentioning
confidence: 99%